Adding saliva testing to oropharyngeal and deep nasal swab testing increases PCR detection of SARS‐CoV‐2 in primary care and children. Issue 6 (20th July 2021) - Oliver, Jane; Tosif, Shidan; Lee, Lai‐yang; Costa, Anna‐Maria; Bartel, Chelsea; Last, Katherine; Clifford, Vanessa; Daley, Andrew; Allard, Nicole; Orr, Catherine; Nind, Ashley; Alexander, Karyn; et al.
Abstract: Objective: To compare the concordance and acceptability of saliva testing with standard‐of‐care oropharyngeal and bilateral deep nasal swab testing for severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) in children and in general practice. Design: Prospective multicentre diagnostic validation study. Setting: Royal Children's Hospital, and two general practices (cohealth, West Melbourne; Cirqit Health, Altona North) in Melbourne, July–October 2020. Participants: 1050 people who provided paired saliva and oropharyngeal‐nasal swabs for SARS‐CoV‐2 testing. Main outcome measures: Numbers of cases in which SARS‐CoV‐2 was detected in either specimen type by real‐time polymerase chain reaction; concordance of results for paired specimens; positive percent agreement (PPA) for virus detection, by specimen type. Results: SARS‐CoV‐2 was detected in 54 of 1050 people with assessable specimens (5%), including 19 cases (35%) in which both specimens were positive. The overall PPA was 72% (95% CI, 58–84%) for saliva and 63% (95% CI, 49–76%) for oropharyngeal‐nasal swabs. For the 35 positive specimens from people aged 10 years or more, PPA was 86% (95% CI, 70–95%) for saliva and 63% (95% CI, 45–79%) for oropharyngeal‐nasal swabs. Adding saliva testing to standard‐of‐care oropharyngeal‐nasal swab testing increased overall case detection by 59% (95% CI, 29–95%). Providing saliva was preferred to an oropharyngeal‐nasal swab by most participants (75%), including 141 of 153 children under 10 years of age (92%). Conclusion: In children over 10 years of age and adults, saliva testing alone may be suitable for SARS‐CoV‐2 detection, while for children under 10, saliva testing may be suitable as an adjunct to oropharyngeal‐nasal swab testing for increasing case detection.